Early time window for memory ensemble allocation specifically depending on activity in Syt2+ early-born parvalbumin interneurons - Sergio Valbuena; Komal Bhandari; Annapoorani Udhayachandran; Matteo Tripodi; Pico Caroni (Cell Reports)
Summary: In learning and memory, the encoding of experience is converted into memory ensembles, affecting future behavior. The mechanisms underlying such memory formation are poorly understood, but parvalbumin-expressing (PV) interneurons might be important due to their roles in shaping offline network activity. Here, we addressed the roles of early- and late-born PV neuron subpopulations in memory formation and consolidation in mice. Subpopulation-specific silencing of early-born Syt2+ hippocampal PV neurons during an early 15-min time window upon learning prevented allocation of cFos expression to the correct learning-related principal neuron (PN) subpopulation and memory formation. Conversely, late-born Syt2− PV neurons were specifically required for subsequent memory consolidation and recall, but not PN allocation. During memory formation, the recruitment of one PN subpopulation prevented the subsequent recruitment of the alternative subpopulation. Therefore, memory ensemble allocation to the correct PN subpopulation is a critical early step in memory formation, specifically depending on the activity of Syt2+ early-born PV neurons.